2018
DOI: 10.48550/arxiv.1807.11364
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The logarithmic Picard group and its tropicalization

Abstract: We construct the logarithmic and tropical Picard groups of a family of logarithmic curves and realize the latter as the quotient of the former by the algebraic Jacobian. We show that the logarithmic Jacobian is a proper family of logarithmic abelian varieties over the moduli space of Deligne-Mumford stable curves, but does not possess an underlying algebraic stack. However, the logarithmic Picard group does have logarithmic modifications that are representable by logarithmic schemes, all of which are obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…More recently, the polytopal decomposition of the tropical Jacobian associated to an Esteves compactified Jacobian is studied in [AP20], as a tropical analogue of the Oda-Seshadri compactified Jacobian. See also [MW18] for related constructions with logarithmic Picard groups.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the polytopal decomposition of the tropical Jacobian associated to an Esteves compactified Jacobian is studied in [AP20], as a tropical analogue of the Oda-Seshadri compactified Jacobian. See also [MW18] for related constructions with logarithmic Picard groups.…”
Section: Introductionmentioning
confidence: 99%
“…A sequel on LogPic and TroPic. In [MW18] the authors have shown that in the category of logarithmic schemes (and stacks), there is a unique minimal model of the universal logarithmic Jacobian that is not representable by an algebraic stack. The study of this so-called universal logarithmic Picard variety LogPic g,n,d can be traced back to Illusie [Ill94] and has subsequently received attention in [Kaj93,Ols04,Bel16,FRTU19].…”
Section: Theorem Cmentioning
confidence: 99%
“…The study of this so-called universal logarithmic Picard variety LogPic g,n,d can be traced back to Illusie [Ill94] and has subsequently received attention in [Kaj93,Ols04,Bel16,FRTU19]. The authors of [MW18] also introduce the universal tropical Picard variety, which universally over M log g,n is denoted by T roPic g,n,d . It parametrizes tropical curves together with a torsor over the sheaf of harmonic or linear functions on Γ of degree d and it naturally arises as the tropicalization of LogPic g,n,d via a natural tropicalization morphism LogPic g,n,d → T roPic g,n,d .…”
Section: Theorem Cmentioning
confidence: 99%
“…Remark 2.1.2. The condition in Definition 2.1.1 says that f pulls back harmonic functions on Γ to harmonic functions on r Γ (see [MZ08,ABBR15,MW18] for more on this point of view).…”
Section: Harmonic Morphisms Let γ and R γ Be Tropical Curves A Contin...mentioning
confidence: 99%